Effect of extraction temperatures on in vitro antioxidant activities of polysaccharides from Ophiocordyceps sobolifera - Khoa, Tran Van; Hieu, Le Trung; Son, Le Lam; Vu, Ho Xuan Anh; Kiet, Trinh Tam; Thi, Tran Thi Van (Hue University Journal of Science: Natural Science, 2019)
The objective of this paper is to evaluate the effects of extraction temperatures on in vitro antioxidant potential of polysaccharides from the Ophiocordyceps sobolifera. The antioxidant capacity of Ophiocordyceps sobolifera polysaccharides was evaluated using 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) as a radical scavenger and the total antioxidant capacity methods. The results show that the highest antioxidant activity of the polysaccharides could be attained at the extraction temperature of 80°C. The total antioxidant capacity of olysaccharides from Ophiocordyceps sobolifera is from 0.1183 ± 0.0011 to 0.1454 ± 0.0021 mg GA/g or from 0.1105 ± 0.0004 to 0.1215 ± 0.0006 μmol AS/g. The polysaccharides have the most potent antioxidant activity with the lowest half‐maximal inhibitory concentration (IC50) value ranging from 0.97 mg/mL to 1.06 mg/mL.